Let a and b be real numbers satisfying a 2 + 2 b 2 = 2 . Find the sum of the minimum and maximum possible values of P = a + 3 b − 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If ( a , b ) satisfy a 2 + 2 b 2 = 2 then so do ( − a , − b ) as ( − a ) 2 + 2 ( − b ) 2 = a 2 + 2 b 2 = 2 . Let ( a , b ) be the values which makes P at its maximum. Let ( x , y ) be values that satisfy a 2 + 2 b 2 = 2 and let P ′ = x + 3 y − 2 . Since ( a , b ) is gives the maximum value of P , we must have P a + 3 b − x + 3 ( − y ) − x + 3 ( − y ) − 2 ≥ P ′ ≥ x + 3 y ≥ − a + 3 ( − b ) ≥ − a + 3 ( − b ) − 2 . This means that for any ( − x , − y ) , − x + 3 ( − y ) − 2 will always be greater than − a + 3 ( − b ) − 2 (with equality holding when ( x , y ) = ( a , b ) ). Thus when the ( a , b ) gives the maximum value of P , ( − a , − b ) will give the minimum value. The sum of P for these two values are a + 3 b − 2 + ( − a ) + 3 ( − b ) − 2 = − 4
Relevant wiki: Cauchy-Schwarz Inequality
One more solution wouldn't hurt. By the cauchy-schwarz inequality,
( 1 2 ) + ( 2 3 ) 2 ) ( ( a ) 2 + ( 2 b ) 2 ) ≥ ( a + ( 2 ) ( 2 3 ) ( b ) ) 2 , giving us
1 1 ≥ ( a + 3 b ) 2
This implies
1 1 ≥ a + 3 b ≥ − 1 1 .
Subtracting 2 from both sides gives us
1 1 − 2 ≥ a + 3 b − 2 ≥ − 1 1 − 2 .
Therefore the maximum is 1 1 − 2 , minimum is − 1 1 − 2 . Our answer is then 1 1 − 2 − 1 1 − 2 = − 4 .
Shortcut based on symmetry
If we replace ( a , b ) by ( − a , − b ) , the value of a 2 + 2 b 2 = 2 remains the same, while the value of P is replaced by − 4 − P . If ( a ⋆ , b ⋆ ) gives a maximum then ( − a ⋆ , − b ⋆ ) gives the minimum, and P m i n = − 4 − P m a x . Thus P m i n + P m a x = − 4 . without knowing any further details!
Suppose ( a , b ) are such that P m a x = a + 3 b − 2 is maximal under the condition a 2 + 2 b 2 = 2 . I claim that the minimum value of P under the same condition is P m i n = ( − a ) + 3 ( − b ) − 2 = − 4 − P m a x .
Proof by contradiction: Suppose that instead there exist ( c , d ) where P reaches a minimum value P m i n = c + 3 d − 2 < − 4 − P m a x , with c 2 + 2 d 2 = 2 . Then ( − c ) 2 + 2 ( − d ) 2 = c 2 + 2 d 2 = 2 ; and ( − c ) + 3 ( − d ) − 2 = − 4 − P m i n > P m a x , but this is impossible because we assumed that under the given condition P m a x was the maximum.
Sir can you please explain why (-a,-b) gives a minima if (a,b) gives maxima?
Thanks.
Relevant wiki: Trigonometry R method
Similar solution as @MS HT's, different presentation.
a 2 + 2 b 2 2 a 2 + b 2 = 2 = 1 Divide both sides by 2 Using the identity sin 2 θ + cos 2 θ = 1
⟹ ⎩ ⎨ ⎧ 2 a = sin θ b = cos θ ⟹ a = 2 sin θ
Then, we have:
P = a + 3 b − 2 = 2 sin θ + 3 cos θ − 2 = 1 1 ( 1 1 2 sin θ + 1 1 3 cos θ ) − 2 = 1 1 sin ( θ + tan − 1 2 3 ) − 2
We note that P is maximum and minimum when sin ( θ + tan − 1 2 3 ) is maximum = 1 and minimum = − 1 respectively. Therefore, P m a x = 1 1 − 2 and P m i n = − 1 1 − 2 , and P m a x + P m i n = − 4 .
Natural approach to this problem would be trigonometric substitution , but just for sake of variety, here's another method.
We have to find minimum and maximum value of P
From given constraint, a 2 = 2 ( 1 − b 2 )
Also, ( P − 3 b + 2 ) 2 = a 2
Therefore, ( P − 3 b + 2 ) 2 = 2 ( 1 − b 2 ) .
Rearranging a bit, we get 1 1 b 2 − 6 b ( P + 2 ) + P 2 + 4 P + 2 = 0
Let us consider the above equation as a quadratic in b .
Since b ∈ R , the discriminant of the quadratic equation ≥ 0
⟹ ( − 6 ( P + 2 ) ) 2 − 4 ( 1 1 ) ( P 2 + 4 P + 2 ) ≥ 0
⟹ − 2 − 1 1 ≤ P ≤ − 2 + 1 1
Therefore final answer is − 4 .
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Trigonometric R method
Thus , a 2 + 2 b 2 = 2 and then rewrite it we got :
2 a 2 + b 2 = 1
Let 2 a = sin x ; b = cos x
So P = 2 sin x + 3 cos x − 2
By R method , the equation has the solution when : ( P + 2 ) 2 ≤ ( 2 ) 2 + 3 2 = 1 1
− 2 − 1 1 ≤ P ≤ − 2 + 1 1
So the sum is ( − 2 − 1 1 ) + ( − 2 + 1 1 ) = − 4 .